Solidification of Thin Liquid Films - Miles, Christopher T. (2020)
Understanding the dewetting and solidification of thin films is key in the fabrication of thin film solar cells, as a device with low percentage of surface coverage will have a greatly diminished efficiency. In this thesis we use Rational Continuum Mechanics to propose a thermodynamically-consistent framework for classes of models describing the evolution of solidifying thin films. Starting from the key laws of the conservation of mass and the first and second laws of thermodynamics, and employing the Coleman-Noll procedure, we derive a class of models for predicting the evolution of a thin liquid film in isothermal settings. We show that models existing in literature and derived using different techniques fit into these classes.